2016
DOI: 10.1016/j.bbagen.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Alpha crystallins in the retinal pigment epithelium and implications for the pathogenesis and treatment of age-related macular degeneration

Abstract: Background αA- and αB crystallins are principal members of the small heat shock protein family and elicit both a cell protective function and a chaperone function. α-Crystallins have been found to be prominent proteins in normal and pathological retina emphasizing the importance for in-depth understanding of their function and significance. Scope of Review Retinal pigment epithelial cells (RPE) play a vital role in the pathogenesis of age-related macular degeneration (AMD). This review addresses a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 99 publications
1
71
0
1
Order By: Relevance
“…Despite differences in experimental approach, all three studies found that patient-derived RPE overexpressed mRNAs and proteins neovascularization. [52][53][54] Under basal conditions, our study demonstrated an increase in annexin A2 mRNA and a decrease in ICAM-1.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Despite differences in experimental approach, all three studies found that patient-derived RPE overexpressed mRNAs and proteins neovascularization. [52][53][54] Under basal conditions, our study demonstrated an increase in annexin A2 mRNA and a decrease in ICAM-1.…”
Section: Discussionmentioning
confidence: 53%
“…αA and αB crystallins belong to a family of heat shock proteins that have been detected in the RPE‐Bruch's membrane‐choroid complex of AMD patients. These proteins may serve to protect RPE cells from oxidative injury but may also play a role in the progression of angiogenesis in choroidal neovascularization . Under basal conditions, our study demonstrated an increase in annexin A2 mRNA and a decrease in ICAM‐1.…”
Section: Discussionmentioning
confidence: 55%
“…26,27 They protect cells from hypoxia and maintain mitochondrial integrity. 26,28 In addition to their neuroprotective role, crystallins also have other roles in vascular biology. 29,30 aB-crystallin functions as a chaperone for VEGFA and is crucial for its proper secretion, which in turn, is crucial for endothelial cell survival in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this decreased autophagy might be the accumulation of lipofuscin, a hallmark of aging; this protein is known to suppress lysosomal function and autophagic clearance in RPE cells (Ryhänen et al 2009;Krohne et al 2010;Viiri et al 2013;Mitter et al 2014;Valapala et al 2014;Zhang et al 2015). Autophagy may regulate the traffic of intracellular proteins in exosomes into the extracellular space, which probably contributes to drusen formation (Wang et al 2009;Kannan et al 2016). The cytoplasms of RPE cells showed sporadic to moderate staining in specimens from the wild type mice whereas the corresponding knock-outs showed only sporadic staining in the groups 10-13 months and younger but almost extensive staining in 18 months old mice.…”
Section: Discussionmentioning
confidence: 98%